Handbook of research on the impacts, challenges, and policy responses to overtourism - Almeida, Cláudia Ribeiro de 1971-; Quintano, Alfred; Simancas, Moisés; Huete, Raquel (IGI Global, 2020)
"This book is a collection of research on best practices and legislation solutions for the management of tourism destinations suffering from overtourism, tourismophobia, or antitourism movement issues"--
Description based on title screen (IGI Global, viewed 03/19/2020)
Keywords: Overtourism; Overtourism / Case studies; Massentourismus